(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In modern conditions, the identification of reliable suppliers for state needs plays a key role in ensuring the effective functioning of state bodies and the implementation of state programs. For this purpose, various ways and methods of assessing potential suppliers are used, including the analysis of their financial stability, experience and reputation in the market, the quality of the goods or services offered, as well as compliance with legislative requirements and standards. Criteria include factors such as financial stability, work experience, product quality, and competitive delivery terms. Evaluation methods include competitive procedures, the use of qualification criteria and preliminary screening of potential suppliers. Effective identification of reliable suppliers helps to increase transparency, reduce risks and ensure the successful implementation of public procurement and programs.